Human characteristics that affect the efficiency of community services in the cities of Al-Mada'in District - Ali, Saja; Aljanabi, Fouad (Al-Adab Journal, 2024)
The research examined the human characteristics that affect the efficiency of community services in the cities of Al-Mada’in District at the year 2022 in order to reveal the reality of the spatial distribution of community services (educational, health, recreational). This study came as a result of the increased requirements of the population in the study area for these services in order to Knowing the strengths and weaknesses and the appropriateness of the distribution and availability of these services in the study area, as the research dealt with studying the most important human factors that affect the efficiency of these services, the most important of which are (population growth, population distribution and density, population composition, which in turn is divided into age composition and gender composition (males, females) And the educational composition to show the impact of these characteristics on the services available in the study area  The study reached a number of conclusions and recommendations, including that the neighborhoods of the study area suffer from a lack of services, and if they are available there, they need to be rehabilitated and distributed in a way that suits the distribution of the population for the purpose of achieving their optimal distribution.